lecture_4 (dragged)

# lecture_4 (dragged) - MA 36600 LECTURE NOTES WEDNESDAY...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: MA 36600 LECTURE NOTES: WEDNESDAY, JANUARY 21 First Order Linear Equations Deﬁnitions. So far we have considered initial value problems in the form dy = −b + a y, y (0) = y0 dt where a and b are constants. We showed that the solution is b b y (t) = + C eat where C = y0 − . a a In general, an ordinary diﬀerential equation is said to be a ﬁrst order equation if it is a relation in the form F (t, y, y ￿ ) = 0. Upon expressing the derivative y ￿ in terms of the other variables, we ﬁnd an expression in the form dy = G(t, y ) dt for some function G(t, y ). We say that a function y = y (t) is a solution if it satisﬁes this equation. If y (t0 ) = y0 is an initial value, we think of the graph of y = y (t) as passing through the point (t0 , y0 ). We say that this ﬁrst order equation is linear if G(t, y ) = g (t) − p(t) y for some functions g (t) and p(t). That is, if the diﬀerential equation is in the form dy + p(t) y = g (t). dt Integrating Factors. Consider the ﬁrst order linear diﬀerential equation dy + p(t) y = g (t). dt Choose a function µ = µ(t). Multiply the ﬁrst order diﬀerential equation above by this function: dy + µ(t) p(t) y = µ(t) g (t). dt Say that we can choose a function µ = µ(t) such that i. µ(t) is not identically zero, and ii. µ￿ (t) = p(t) µ(t). Then we would have dy dy dµ d µ(t) + µ(t) p(t) y = µ(t) · + · y (t) = [µ(t) y (t)] dt dt dt dt This gives the diﬀerential equation ￿t d [µ(t) y (t)] = µ(t) g (t) =⇒ µ(t) y (t) = µ(τ ) g (τ ) dτ + C dt µ(t) for some constant C . (We use this notation to remind ourselves that the indeﬁnite integral of a function is really a function of t, not the dummy variable of integration τ .) Before we continue, we study conditions (i) and (ii) in more detail. If µ = µ(t) is not identically zero, we can divide by it: dµ 1 dµ = p(t) µ =⇒ = p(t). dt µ dt The left-hand side is a derivative: 1 dµ d d = ln |µ| =⇒ ln |µ| = p(t). µ dt dt dt 1 ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online